2017
DOI: 10.1080/14697688.2017.1353127
|View full text |Cite
|
Sign up to set email alerts
|

On VIX futures in the rough Bergomi model

Abstract: Abstract. The rough Bergomi model introduced by Bayer, Friz and Gatheral [3] has been outperforming conventional Markovian stochastic volatility models by reproducing implied volatility smiles in a very realistic manner, in particular for short maturities. We investigate here the dynamics of the VIX and the forward variance curve generated by this model, and develop efficient pricing algorithms for VIX futures and options. We further analyse the validity of the rough Bergomi model to jointly describe the VIX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 17 publications
1
40
0
Order By: Relevance
“…In this section we show and comment some plots related to the estimation of VIX Futures prices. We set the values H = 0.1 and ν = 1.18778 for the parameters and investigate three different initial forward variance curves v 0 (•), as in [22]: Scenario 1. v 0 (t) = 0.234 2 ; Scenario 2. v 0 (t) = 0.234 2 (1 + t) 2 ; Scenario 3. v 0 (t) = 0.234 2 √ 1 + t.…”
Section: Pricing and Comparison With Monte Carlomentioning
confidence: 99%
See 2 more Smart Citations
“…In this section we show and comment some plots related to the estimation of VIX Futures prices. We set the values H = 0.1 and ν = 1.18778 for the parameters and investigate three different initial forward variance curves v 0 (•), as in [22]: Scenario 1. v 0 (t) = 0.234 2 ; Scenario 2. v 0 (t) = 0.234 2 (1 + t) 2 ; Scenario 3. v 0 (t) = 0.234 2 √ 1 + t.…”
Section: Pricing and Comparison With Monte Carlomentioning
confidence: 99%
“…In all these cases, v 0 is an increasing function of time, whose value at zero is close to the square of the reference value of 0.25. One of the most recent and effective way to compute the price of VIX Futures is a Monte-Carlo-simulation method based on Cholesky decomposition, for which we refer to [22,Section 3.3.2]. It can be considered as a good approximation of the true price when the number M of computed paths is large.…”
Section: Pricing and Comparison With Monte Carlomentioning
confidence: 99%
See 1 more Smart Citation
“…Still, [31] showed that the rough Bergomi model is too close to lognormal to jointly calibrate both markets. Its younger sister [30] added a stochastic volatility of volatility component, generating a smile sandwiched between the bid-ask prices when calibrating VIX, but the joint calibration is not provided.…”
Section: Introductionmentioning
confidence: 99%
“…In order to price options under an rBergomi model, Bayer et al [6] proposed hierarchical adaptive sparse grids, Jacquier et al [7] developed pricing algorithms for VIX futures and options, and McCrickerd and Pakkanen [8] developed a "turbocharged" Monte Carlo pricing method. A number of short-term approximations have been proposed to obtain fast approximations for short maturities-see, for example, Fukasawa [3], El Euch et al [9], Bayer et al [10], and Friz et al [11].…”
Section: Introductionmentioning
confidence: 99%